Stigma When There Is No Other Option: Understanding How Poverty Fuels Discrimination toward People Living with HIV in Zambia - Bond, Virginia (International Food Policy Research Institute, 2006)
Based on qualitative fieldwork in urban and rural Zambia (see Bond et al. 2003), this chapter aims to demonstrate that HIV-related stigma and discrimination are fueled by the practicalities of limited resources and narrow options and, in this wider context of poverty and household fatigue, that the poor, women, orphans, and rural dwellers are particularly vulnerable to HIV-related stigma and discrimination. It is apparent that a significant proportion of discriminatory actions are caused by the fact that HIV and AIDS can be so very hard to manage in the context of poverty. Significant differences between the urban and rural sites that emerged in our material, with overall less stigma manifested in the urban site and more pronounced stigma in the rural site, suggest that it is possible to alleviate household stress and reduce this type of stigma and discrimination by providing services and support.